Optimizing CAD Pattern Making Learning Through the Development of Video Learning Media in the Family Welfare Education Study Program - Hazevi Atila Yazel Aze; Ernawati; Hadiastuti; Nabila Zafira (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
The use of Computer-Aided Design (CAD) software in fashion pattern making, particularly CAD Pattern Making, provides opportunities for students to develop their digital design skills. However, not all students are able to understand the pattern making process, such as camisole patterns using the CAD Pattern Making application. Most students experience difficulties in applying theory to practice and feel less confident due to limited references on the use of these tools and software. This study aims to develop video learning media as a medium in CAD Pattern Making courses to minimize the difficulties students face in understanding the concepts and practices of pattern making. This study uses a qualitative approach with 30 third-semester students from the Family Welfare Education Study Program as research subjects. Data collection techniques included interviews, observations, direct observation, and activity documentation. The learning videos developed covered several key elements, including: learning objectives, introduction to the features or tools used, steps for making patterns, and practical tips for making digital camisole patterns. The results of the study indicate that instructional videos can optimize the practical learning process. Students find it easier to understand the use of software features, such as point determination, measurement, line joining, and pattern simulation. These findings indicate that visual media are more effective than lectures or printed teaching materials in explaining the technical concepts of CAD Pattern Making.